Smoking, Porphyromonas gingivalis and the immune response to citrullinated autoantigens before the clinical onset of rheumatoid arthritis in a Southern European nested case–control study. Issue 1 (December 2015) - Fisher, Benjamin; Cartwright, Alison; Quirke, Anne-Marie; de Pablo, Paola; Romaguera, Dora; Panico, Salvatore; Mattiello, Amalia; Gavrila, Diana; Navarro, Carmen; Sacerdote, Carlotta; Vineis, Paolo; Tumino, Rosario; et al.
Abstract Background Antibodies to citrullinated proteins (ACPA) occur years before RA diagnosis.Porphyromonas gingivalis expresses its own peptidylarginine deiminase (PPAD), and is a proposed aetiological factor for the ACPA response. Smoking is a risk factor for both ACPA-positive RA and periodontitis. We aimed to study the relation of these factors to the risk of RA in a prospective cohort. Methods We performed a nested case–control study by identifying pre-RA cases in four populations from the European Prospective Investigation into Cancer and nutrition, matched with three controls. Data on smoking and other covariates were obtained from baseline questionnaires. Antibodies to CCP2 and citrullinated peptides from α-enolase, fibrinogen, vimentin and PPAD were measured. Antibodies to arginine gingipain (RgpB) were used as a marker forP.gingivalis infection and validated in a separate cohort of healthy controls and subjects with periodontitis. Results We studied 103 pre-RA cases. RA development was associated with several ACPA specificities, but not with antibodies to citrullinated PPAD peptides. Antibody levels to RgpB and PPAD peptides were higher in smokers but were not associated with risk of RA or with pre-RA autoimmunity. Former but not current smoking was associated with antibodies to α-enolase (OR 4.06; 95 % CI 1.02, 16.2 versus 0.54; 0.09-3.73) and fibrinogen peptides (OR 4.24; 95 % CI 1.2-14.96 versus 0.58; 0.13-2.70), and later development of RA (OR 2.48; 95 % CI 1.27-4.84 versus 1.57; 0.85-2.93), independent of smoking intensity. Conclusions Smoking remains a risk factor for RA well before the clinical onset of disease. In this cohort, P.gingivalis is not associated with pre-RA autoimmunity or risk of RA in an early phase before disease-onset. Antibodies to PPAD peptides are not an early feature of ACPA ontogeny.